Thermal evolution of the mechanical properties of calcareous earthenware - Serra, Maria Florencia (2014)
Calcareous earthenware is used very frequently for tableware, and fired twice between 980 °C and 1040 °C. Before firing it mostly consists in a kaolinitic clay accompanied by quartz and ≈7 wt% of carbonates (Ca and Mg) as fluxing fraction. In this article the firing temperature correlation with the textural, structural and mechanical properties was established in the 700–1100 °C firing range. Materials fired between 800 and 1050 °C presented an interesting correlation between the processing variable (temperature) and the evaluated properties. The porosity in this range was almost constant however the properties evolved exponentially with the temperature. A parallel behavior between flexural strength, diametral compression resistance and dynamic elastic modulus was observed. Furthermore within the technological temperature range the correlation was linear. Finally the incorporation of the porosimetric analysis performed permitted to understand that the firing processes of calcareous earthenware below 1050 °C is not strictly a sintering process with a gradual densification and loss of porosity: it should be considered as a series of complex chemical processes accompanied by a textural evolution of pore size increase with no important porosity decrease. Only for higher temperature treatments (which exceed the technological ones) the porosity diminishes abruptly. When this reduction takes place, it is accompanied by an increment in the mechanical properties figures and a loss in the dimensional stability.